2019
DOI: 10.3389/fphys.2019.01254
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan and Kynurenine Pathway Metabolites in Animal Models of Retinal and Optic Nerve Damage: Different Dynamics of Changes

Abstract: Kynurenines, products of tryptophan (TRP) metabolism, display neurotoxic (e.g., 3-hydroxykynurenine; 3-HK), or neuroprotective (e.g., kynurenic acid; KYNA) properties. Imbalance between the enzymes constituting the kynurenine pathway (KP) plays a role in several disease, including neurodegeneration. In this study, we track changes in concentrations of tryptophan and its selected metabolites after damage to retinal ganglion cells and link this data with expression of KP enzymes. Brown-Norway rats were subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…S1 ). These metabolites induce exictotoxicity and cause neuronal and retinal ganglion cell death 64 , 65 . Previous studies have also reported elevated levels of ATP and glutamate in glaucoma 38 , 66 .…”
Section: Discussionmentioning
confidence: 99%
“…S1 ). These metabolites induce exictotoxicity and cause neuronal and retinal ganglion cell death 64 , 65 . Previous studies have also reported elevated levels of ATP and glutamate in glaucoma 38 , 66 .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, tryptophan was metabolized to kynurenine, and its concentration was decreased in the abovementioned models. The concentration of kynurenine, the product of tryptophan metabolism, was reciprocally increased [ 24 ]. It was reported that a higher IDO expression was observed in NPDR patients than in NDR patients; interestingly, an even higher IDO expression was observed in PDR versus NPDR patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous results also demonstrated changes in retinal KYNA in two surgical models of glaucoma. A complex response was noted after NMDA administration (a transient increase 2 days after NMDA injection and then a decrease) and a massive decrease of retinal KYNA concentration due to partial optic nerve crush [ 14 ]. The decrease in KYNA concentration observed in this study seems to be an effect of KP failure.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia activation was previously shown to be an early event in the course of glaucomatous pathology in DBA/2J mice and to correlate with the severity of neurodegeneration in these mice [ 44 ]. We have also recently shown that KMO is overexpressed in two animal models of glaucoma: optic nerve crush and NMDA-induced RGC loss [ 14 ]. Interestingly, the dynamics of changes differed in these two animal models (peak expression 12 h after crush and 48 h after intravitreal NMDA administration).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation